Unveiling the Dynamics of the Jirga System in Pakistan: An In-Depth Analysis - Ahmed, Taniya; Ahmed, Khurshid; Khan, Muhammad Arif (Annals of Human and Social Sciences, 2024)
The Jirga system in Pakistan holds great significance as it manages support to the grieving and punishes wrongdoers. However, it violates constitutional laws and disregards fundamental human rights when settling conflicts. To comprehend the dynamics of a Jirga, extensive research must be conducted on such topics. The study is based upon two objectives which aimed at identifying the Jirga system's flows while resolving conflicts in various regions of Pakistan, and to gain insight into alternative dispute resolution (ADR) initiatives offered in various countries. The study employs a qualitative research methodology and collected data from various secondary sources. It was revealed that the Jirga is unjust and violates every human right. Meanwhile, (ADR) programs, focus on transparent and equitable conflict settlement while operating lawfully. The paper provided recommendations such as encouraging the Jirga system to be formally recognized by law with well-defined procedures that will allow it to handle disputes effectively and maintain societal stability.